RE-DESIGN DAN PENANGANAN BREAKWATER DI PELABUHAN BATANG - Ari Surya Bawono; Rizki Indianto; Indrastono Dwi Atmanto; Bambang Pardoyo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Onshore espescially needed a prevention to sea water abration towards the geomorfology of shore. The Ones of prevention is build a breakwater. Breakwater must be analyst for strong to prevent from sea water pressure are come from the sea wave. That analyst include condition where on slope occured landslide are make The building collapse. On this analyst is settle The manual analysis of slope stability with Fellenius method and Plaxis analisys for breakwater on sta 00+350 in Ports of Batang Districs. Result of this analyst is generate 1.25 < Safety of Factor < 1.4 is determined that The slope stability on breakwater is safe but not stable and The handling solution based on construction is used The bore-pile foundation Ø800mm with depth 24 m from seabed and elevation step construction.